Pengaruh Pelatihan dan Pengembangan Serta Prestasi Kerja terhadap Pengembangan Karir Pegawai Pada Dinas Koperasi Usaha Mikro Kecil Menengah Banjarmasin - Gerhana, Wida (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2017)
The Effects of Training and Development and Work Achievement on Employees Career Development at the Department of Cooperatives, Micro, Small and Medium Enterprises in Banjarmasin. The purpose of this study is to investigate employees opinions on the effect of training and development and work achievement on employees career development. The populations in this study were 30 employees. The census method was used with the quantitative descriptive and explanatory research as its type of the study. Explaining the relationship of the effect of training and development and work achievement on employees career development was used the multiple regression analysis. In order to test the hypothesis simultaneously, F-test has been used, while t-test has been used to test the hypothesis partially. The result showed that simultaneously and partially, the implementation of training and development and work achievement had a significant positive effect on employees career development at the Dinas Koperasi Usaha Mikro Kecil Menengah in Banjarmasin. Both variables contributed 50.6%, work achievement gave a greater influence than the training and development on employees career development, even though the training and development also contributed in giving an influence.Keywords : training and development, work achievement, career development